RESPONSIBILITY OF INSURANCE COMPANIES DECLARED BANKRUPT FOR THE REPAYMENT OF POLICYHOLDERS' RECEIVABLES - Ni Made Dharmika Yogiswari; I Wayan Novy Purwanto (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
Insurance companies, as legal entities engaging in business activities, may not always maintain good financial standing. A bankrupt company is typically in a state of insolvency where its assets fall short of its outstanding obligations. The insolvency of an Insurance Company leads to setbacks and limitations in its operations, with the Policyholder being the most affected party. This study aims to explore how dividends from bankrupt insurance companies are distributed and how such companies are accountable for settling Policyholders' receivables. The research employs a normative research method, utilizing a statutory approach and legal concept analysis. The findings indicate that the distribution of bankrupt insurance companies' assets is based on the priority order of creditors. The Policyholder, as the Preferred Creditor, receives payment of their receivables first and assumes the position of Separatist Creditor. In case of bankruptcy, the Insurance Company bears full responsibility for settling Policyholders' receivables. If there are any unpaid receivables, the Insurance Company is obligated to pay the remaining amount to the Policyholder.